Relationship between 25-Hydroxy Vitamin D Levels and Type of Morbus Hansen - Theresia L. Toruan; Mutia Devi; Theodorus; Allin Marlina Rivai (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Morbus Hansen is a chronic granulomatous infection of Mycobacterium leprae (M. leprae) which is characterized by cardinal signs in the form of numbness of the skin, thickening of peripheral nerves and acid-fast bacteria (AFB) were found on bacterioscopic examination. WHO has classified MH into paucibasilar MH (MH-PB) and multibasilar MH (MH-MB) based on the number of skin lesions or bacterial index (IB). Vitamin D in MH is known to act as an immunomodulator. This study aims to determine the relationship between serum 25(OH)D levels with Morbus Hansen type at RSUP Dr. Mohammad Hoesin and Leprosy Hospital Dr. Rivai Abdullah Palembang. Methods: A laboratory observational study with a case series design was undertaken at the Dermatology and Venereology (DV) Polyclinic of Infectious Dermatology (DI) Mohammad Hoesin Hospital Palembang since December 2019 to January 2020. A sample of 33 patient MH met the inclusion criteria, consisting of 22 patients with Morbus Hansen (MH) type MB and 11 patients with Morbus Hansen (MH) type PB. Comparison of serum 25(OH)D levels between MB and PB type MH patients was analyzed using the Independent T Test, the relationship between serum 25(OH)D levels and MH type was analyzed using the Fisher Exact Test and the correlation between serum 25(OH)D levels with type of MH was analyzed using Spearman Rho's test. Data analysis using SPSS version 22.0. Results: In this study, there were no differences in demographic characteristics of gender, age, age category, body mass index, education and occupation between MB and PB type MH patients (p > 0.05). There were no difference in duration of therapy (p = 0.155), ENL reaction (p = 0.276) and patient status (p = 0.304) between MB and PB type MH patients, but there were differences in bacterial index (p = 0.000) and clinical spectrum (p = 0.000) between MB and PB type MH patients. There is a difference in the mean level of 25(OH)D between MB and PB type MH patients (p = 0.006), there is a significant relationship between 25 (OH)D levels and MH type patients, (OR = 9.643 ; p = 0.010) and there is a significant moderate positive correlation between levels of 25 (OH)D and the type of MH (r = 0.467; p = 0.006). Conclusion: It can be concluded that there are differences in serum 25(OH)D levels among Morbus Hansen type. In addition, there is a significant relationship between serum 25(OH)D levels with Morbus Hansen type.